2019
DOI: 10.18502/ijnl.v18i3.1636
|View full text |Cite
|
Sign up to set email alerts
|

Role of dimethyl fumarate in the treatment of glioblastoma multiforme: A review article

Abstract: Glioblastoma multiforme (GBM), the most frequent malignant and aggressive primary brain tumor, is characterized by genetically unstable heterogeneous cells, diffused growth pattern, microvascular proliferation, and resistance to chemotherapy. Extensive investigations are being carried out to identify the molecular origin of resistance to chemo- and radio-therapy in GBM and find novel targets for therapy to improve overall survival rate. Dimethyl fumarate (DMF) has been shown to be a safe drug with limited shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…HGG is considered a challenging subtype of brain tumors with a poor prognosis, aggressive features and lack of targeted therapies. Although many efforts have been made to develop effective treatments, tumor heterogeneity and unknown contexts remain limitations of discovered therapies [ 15 ]. Identification of the key genes and pathways involved in HGG pathogenesis is of particular importance to develop new therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…HGG is considered a challenging subtype of brain tumors with a poor prognosis, aggressive features and lack of targeted therapies. Although many efforts have been made to develop effective treatments, tumor heterogeneity and unknown contexts remain limitations of discovered therapies [ 15 ]. Identification of the key genes and pathways involved in HGG pathogenesis is of particular importance to develop new therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Dimethyl fumarate is used in the management of relapsing-remitting multiple sclerosis and psoriasis [ 15 , 70 ]. The drug reduces inflammation and suppresses immune cell function [ 15 ].…”
Section: Drugs Under Clinical Investigationmentioning
confidence: 99%
“…Preclinical studies in tumor models have also shown significant antitumor activity of DMF, which has been linked to its ability to activate Nrf2 and inhibit the NF-κB pathways [214,215] . Promising results have been observed with DMF in several types of cancer models such as glioblastoma, breast cancer, KRAS mutated cancers and myelogenous leukemia [216][217][218][219] . However, to our knowledge, the efficacy of DMF in prostate cancer patients, and especially, its ability to suppress CRPC progression has not been investigated so far.…”
Section: Repurposed Agentsmentioning
confidence: 99%